Kinerja Pengaruh Lalu Lintas Kendaraan Bermotor dan Faktor Lingkungan Terhadap Kadar CO Ambien di Jalan Malioboro, Yogyakarta - Ali, Syaukat (Fakultas Teknik , UGM, 2002)
The aim or the present study is to elucide the influence of the motor vehicles in the traffic factore and various environmental factors with the ambient CO in Malioboro, Yogyakarta